Discover new knowledge and insights with IDNLearn.com's extensive Q&A database. Discover comprehensive answers from knowledgeable members of our community, covering a wide range of topics to meet all your informational needs.

If f (x)=x 3 + 2x 2 - 3, what is f (-1)?

Sagot :

Answer:

f(x)= x³+2x²-3

f(-1)= (-1)³+2(-1)²-3 = -1+2-3 = -4+2 = -2

f(-1)= -2 is the right answer.

Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com is committed to providing the best answers. Thank you for visiting, and see you next time for more solutions.